Pemetaan Sebaran Nasabah Kredit di Lembaga Perkreditan Desa Adat Mengwitani Berbasis Sistem Informasi Geografis (SIG) Menggunakan Python - Yajmana, Dewa Gede Indra; I kadek Andy Asmarajaya; Ida Ayu Utari Dewi (RESI : Jurnal Riset Sistem Informasi, 2025)
Lembaga Perkreditan Desa (LPD) is a microfinance institution owned by traditional villages in Bali, which provides savings and loan services to the community. This study aims to design and develop a Geographic Information System (GIS) to map the distribution of credit customers at LPD Desa Adat Mengwitani. The system was developed using the Waterfall model, which includes the stages of analysis, design, implementation, and testing. The technology used includes the Python programming language with the Flask framework and the Folium library for interactive map visualization. Customer data is stored in a MySQL database and connected using SQLAlchemy. System testing was carried out using the black box testing method, and the results showed that the system performed well without any bugs. The final product is a web-based application that displays an interactive map with customer location markers and customer information in popups. This system helps LPD monitor customer distribution visually and supports decision-making related to credit service and management.